Antioxidating effect of Ampelocissus sp. (Isi Nyaru) on streptozotocin-induced diabetic Rats / Elly Zulaikha Zamri - Elly Zulaikha , Zamri (2020)
The Ampelocissus sp. locally known as Isi Nyaru has been traditionally used by native Malaysian for medical purpose. The tuber was extracted with hexane, petroleum-ether, chloroform, methanol and water solvents. The seperation and detection of bioactive compounds were done using Thin Layer Chromatography (TLC) and Gas Chromatography Mass Spectrometry (GCMS) methods. The TLC results showed the presence of phenolic acids, flavonoids and terpenoids. While in GCMS has revealed the presence of hydrocarbon groups such as alkene, ester and ether, amino acid groups, dicarboxylic acid and cyclic aromatic compound. The total phenol content and total flavonoid content were highest in methanolic extract at 748.50 ± 0.01 mg (TAE)/g and 27.08 ± 0.04 mg (QE)/g respectively. The extracts were tested for antioxidant activities by DPPH radical scavenging activity, ferrous ion chelating activity (FCA) assays and ferric reducing antioxidant power (FRAP) assays. The methanol and water extracts rich in phenol and flavonoid based on Thin Layer Chromatography (TLC) result, exhibit the strongest antioxidant activities to DPPH, FCA and FRAP. According to IC50 reading of DPPH and FCA, methanol extract indicated 1.27 μg/mL and 1.72 μg/mL respectively while water extract indicated 1.22 μg/mL and 1.62 μg/mL respectively. The FRAP value for water extract is 11.73 mmol/g and 11.58 mmol/g for methanol extract. The Streptozotocin (STZ) diabetic-induced rats have been treated by 4000 mg/kg of methanol extract in acute oral toxicity test with no toxicity effects observed in rats. Methanol extract has been chosen for the anti-diabetic treatment of diabetic rats based on its free toxicity effects and has the largest yield production. The blood glucose concentration of methanolic-treated diabetic rats showed the significant reduction which 17.4% (800 mg/kg methanol extract) and 12.4% (800 mg/kg methanol extract), while 21% reduction in glibenclamide-treated diabetic rats. There are slightly increased of body weight in diabetic rats treated with 800 mg/kg and 400 mg/kg methanol extract and glibenclamide which are 1.7%, 2.6% and 3.3% respectively. The activity of antioxidant enzymes which are catalase (Cat) and glutathione peroxidase (GPx) in diabetic rats showed a positive result when treated with extracts and standard. The results concluded that the antioxidant activity of methanol extract was primarily due to the high amount of phenolic and flavonoid content.